Mityczna historia. Czas w Podróży komediantów i Spojrzeniu Odyseusza Teo Angelopulosa - Sławnikowski, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The article centres on two films by Theo Angelopoulos, The Travelling Players and Ulysses’ Gaze, which are analysed with respect to time and with a particular emphasis on the issue of mythical and historical time. Crucial to the presentation of the temporal structure of the films are techniques such as the “editing of time” and foregrounding of duration through the use of long takes. Mythical time is analysed with reference to the theories of myth developed by Mircea Eliade and Claude Lévi-Strauss, which help to show how Angelopoulos melds together the two seemingly mutually exclusive times. Historical time is examined with reference to Krzysztof Pomian’s theory of time. Interpretative conclusions derived from that theory relate to the differences between the two films’ approach to representing history, with The Travelling Players using hindsight for a historiosophical synthesis of Greek history and Ulysses’ Gaze portraying an inability of such synthesis without hindsigh.